The brachial plexus branches to the pectoral muscles in adult rats: morphological aspects and morphometric normative data - Riva, Nilo; Domi, Teuta; Lopez, Ignazio D.; Triolo, Daniela; Fossaghi, Andrea; Dina, Giorgia; Podini, Paola; Comi, Giancarlo; Quattrini, Angelo (Frontiers in Neuroanatomy, 2012)
Animal models provide an important tool to investigate the pathogenesis of neuromuscular disorders. In the present study, we analyze fiber composition of the brachial plexus branches to the pectoral muscles: the medial anterior thoracic nerve and the lateral anterior thoracic nerve. The morphological and morphometric characteristics and the percentage of motor fibers within each nerve are here reported, adding information to microscopic anatomy knowledge of the rat brachial plexus. As control, we employed the quadriceps nerve, commonly used for the evaluation of motor fibers at hindlimbs. We demonstrated that the medial anterior thoracic nerve and the lateral anterior thoracic nerve are predominantly composed of large motor fibers and therefore could be employed to evaluate the peripheral nervous system involvement at forelimbs in neurological diseases models, predominantly affecting the motor fiber compartment.